Exogenous salicylic acid alleviates water stress in watermelon plants - Silva, Joanderson Marques; Silva Júnior, Gabriel Barbosa da; Bonifácio, Aurenivia; Dutra, Alexson Filgueiras; Prado, Renato de Mello [UNESP]; Alcântara Neto, Francisco de; Zuffo, Alan Mario; Melo, Rafael Silva; Pereira, Tássyla Lohanne de Sousa; Sousa, Ricardo Silva de (Wiley, 2022)
Salicylic acid (SA) has been considered to attenuate the effects of abiotic stresses on plants, including water deficit that intensely affects the growth and production of plants. The goal of this work was to evaluate the role of SA in the alleviation of water stress in watermelon seedlings on a morphophysiological and biochemical level. The experiment consisted of application of SA at concentrations of 0, 0.25, 0.50, 0.75 and 1.0 μmol L−1 to leaves of watermelon seedlings grown in three levels of water retention (100%, 75% and 50% WRL). To evaluate the effect on morphophysiological and biochemical aspects, the plant height, leaf area, shoot and root dry weight, chlorophyll index, relative water content, electrolyte leakage, protein content, amino acids, proline, carbohydrates, sucrose and starch concentration variables were determined. All variables were influenced by the SA concentrations and WRL, with statistically significant interaction between these factors for all except root dry weight. SA promotes increases in the concentration of organic solutes and reduces the rate of electrolyte leakage in watermelon seedlings, thus, supporting metabolism and growth of plants under stress conditions resulting from water deficit.
Keywords: abiotic stress; Citrullus lanatus; mitigation; organic solutes; phytohormone